The Implementation of Clique Strategy in Regrouping Program to Increase Farmer’s Interest and Loyalty in Sugarcane Farming - Danang Permadhi; Trikuntari Dianpratiwi (JOURNAL OF SOCIOECONOMICS AND DEVELOPMENT, 2019)
The area size of sugarcane planting nationally shows a decrease. This is also marked by a decrease in the interest of farmers planting sugarcane and low loyalty to the sugar factory. In 2014, the government established a sugarcane management regrouping program. The regrouping program provides benefits for the efficiency of sugarcane planting, more effective in cutting and transport processes, forging farmer group and sugar factory, and increasing farmers' loyalty to the sugar factory.  The weakness of the regrouping program is that it emphasizes technical aspects only. The criterion of the social aspect is essential because this always saves problems related to communication networks and establishing cooperation. Through the clique strategy, this can conduct a communication network analysis in regrouping. Regrouping programs can build social interaction and communication networks. The form and level of communication network structure in the regrouping program can place actors or farmers build communication networks and cooperate in sugarcane farming. Understanding the role of cooperation networks between farmers or groups determines the success of regrouping sugarcane.JEL Classification:  P32, O35, Q18